Determinants Of Quick Response Code Indonesian Standard As Digital Payment Technology On Behavior Intention - Hadmar, A Yaumil Mahsyar; Susanti, Beny (Forum Kerjasama Pendidikan Tinggi, 2025)
The rapid growth of digital payments in Indonesia is marked by the increasing popularity of the Quick Response Code Indonesian Standard (QRIS). Generation Z, as a demographic group highly familiar with digital technology, plays a significant role in driving the adoption of QRIS. This study aims to identify the factors influencing Generation Z's intention to use QRIS as a digital payment method in Indonesia. Using the UTAUT2 model, this study analyzes the influence of performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, and habit on behavior intention. Data was collected through an online questionnaire from 100 Generation Z respondents. Data analysis methods used include instrument testing, classical assumption testing, multiple linear regression, hypothesis testing, and coefficient of determination. The results showed that performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, and habit have a partial and simultaneous influence on behavior intention. The findings of this study have important implications for businesses and policymakers in promoting the adoption of QRIS among the younger generation.